THEAFLAVIN MENGHAMBAT DIFERENSIASI PREADIPOSIT VISERAL MANUSIA MELALUI PPARγ γγ γSECARA IN VITRO - Indra, Rasjad (Jurnal Kedokteran Brawijaya, 2007)
Differentiation of pre-adipocytes into adipocytes, is a complex process that involves coordination of  expression of specific genes and proteins associated with each stage of differentiation. This process is regulated by several signaling pathways. CCAAT element-binding proteins (C/EBP)  αand  βand sterol response element-binding protein 1 (ADD1/SREBP1) are active during the early stages of the differentiation process and induce the expression and/or activity of the peroxisome proliferator-activated receptor  γ(PPARγ), a pivotal coordinator of adipocyte differentiation. Recently, many biological effects of black tea have been reported and these effects may be partially related to its antioxidant  properties. The recent study showed that black tea flavonoids inhibited adipocyte differentiation. The aim of this study was to investigate the role of theaflavin, a flavonoids in black tea, in inhibiting adipocyte differentiation through inhibition of PPARγexpression. Preadipocytes were incubated in media containing standard-differentiated stimulator: Insulin, dexamethasone, IBMX and FBS. After 24 hours, preadipocytes culture media wasadded with theaflavin 50, 100, or 200  µM. The cells were harvested after TF incubation for 24 hours and then the expression of PPARγwas identified by immunocytochemistry and Western blot.